ASSESSMENT OF THE EFFECT OF NATURAL ZEOLITE ON THE MORPHOLOGICAL AND HISTOLOGICAL STATUS OF THE INTERNAL ORGANS OF AFRICAN CATFISH (CLARIAS GARIEPINUS) - А. Osserbay; A. Akkozova; N. Nurkhojayev; S. Junisbayeva; Е. Abildabek (Animal Health and Biosafety, 2026)
This study presents the results of a histopathological examination of the internal organs (liver and intestine) of African catfish (Clarias gariepinus) following dietary supplementation with natural zeolite. The aim of the study was to evaluate the effect of a zeolite based feed additive on the morphofunctional condition of the liver and intestine of fish reared under intensive aquaculture conditions. The experiment was conducted at a fish farming enterprise in the Turkestan Region (Kazakhstan). Two experimental groups were formed: a control group fed a standard diet and an experimental group fed the same diet supplemented with 5% natural zeolite. The feeding trial lasted 82 days under identical hydrochemical and temperature conditions. Fish were fed three times daily according to their body weight. Histopathological examination included both macro- and microscopic evaluation of the liver and intestine. Tissue samples were fixed in 10% neutral buffered formalin, processed using standard histological techniques, embedded in paraffin, sectioned at 5-7 μm, stained with hematoxylin and eosin, and examined using light microscopy. Histological examination of the control group revealed pronounced pathological alterations in the liver, including fatty degeneration of hepatocytes, peripheral displacement of nuclei, and disruption of the hepatic architecture. In the intestine, inflammatory changes, deformation of the intestinal villi, and hemorrhagic infiltration were observed. In contrast, fish receiving dietary zeolite exhibited better preservation of the liver and intestinal morphology, characterized by well-developed intestinal villi, preservation of epithelial integrity, a well-developed muscular layer, and a relatively uniform distribution of goblet cells. The obtained findings suggest that dietary supplementation with natural zeolite is associated with less pronounced morphological alterations in the liver and intestine compared with the control group. However, since the present study was qualitative and comparative in nature, further investigations involving quantitative morphometric assessment are required to confirm these observations.